1998
DOI: 10.2307/176587
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Bacteria into Food Webs: Studies with Sarracenia purpurea Inquilines

Abstract: Predation can have both direct and indirect effects on the population dynamics and community structure of freshwater plankton communities, but its effects on the bacterial component of aquatic systems are less well known. We used a series of laboratory reconstructions of the detritus-based food web in the leaves of the northern pitcher plant Sarracenia purpurea to test the hypothesis that interactions at higher trophic levels could control bacterial densities and community structure. The typical pitcher commun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
159
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(167 citation statements)
references
References 65 publications
6
159
1
Order By: Relevance
“…Container habitats of mosquitoes are ecosystem mesocosms that are analogous to aquatic ecosystems that naturally occur in tree holes and other plant cavities [20]. These aquatic habitats support food webs that are dependent on detritus [8] and microbial communities that metabolize and mineralize organic carbon from detritus [29]. Based on sequence analysis of 16S rDNA amplicons, our investigation revealed that human-made water-filled containers and tree holes hold bacterial communities of mainly undescribed species.…”
Section: Discussionmentioning
confidence: 99%
“…Container habitats of mosquitoes are ecosystem mesocosms that are analogous to aquatic ecosystems that naturally occur in tree holes and other plant cavities [20]. These aquatic habitats support food webs that are dependent on detritus [8] and microbial communities that metabolize and mineralize organic carbon from detritus [29]. Based on sequence analysis of 16S rDNA amplicons, our investigation revealed that human-made water-filled containers and tree holes hold bacterial communities of mainly undescribed species.…”
Section: Discussionmentioning
confidence: 99%
“…At the local (pitcher) scale, species diversity of many microscopic organisms (bacteria, rotifers and protozoa) is strongly affected by both TOP-DOWN (mosquito occurrence) and BOTTOM-UP (carcass provisioning) processes [7,9,13,22,46]. Mosquito occurrence at the pitcher scale is affected by bottom-up effects, such as carcass provisioning [43], carcass processing by midges [47] and pitcher size [43,48].…”
Section: Microcosms: Why Go Natural?mentioning
confidence: 99%
“…However, predators influence the diversity and abundance of some taxa (often other predators) living in the water held by pitcher plants (Addicott 1974;Cochran-Stafira and von Ende 1998), bromeliads (e.g., Lounibos et al 1987), Heliconia spp. bracts (Naeem 1988), bamboo stumps (Sota and Mogi 1996), and tree holes (e.g., Bradshaw and Holzapfel 1983;Fincke et al 1997;Nannini and Juliano 1998).…”
Section: Introductionmentioning
confidence: 99%